Atomistic calculations of the generalized stacking fault energies in two refractory multi-principal element alloys. (September 2020) - Xu, Shuozhi; Hwang, Emily; Jian, Wu-Rong; Su, Yanqing; Beyerlein, Irene J.
Abstract: In this work, we utilize atomistic simulations to calculate the generalized stacking fault energies (GSFEs), which are related to the dislocation glide process, on four types of slip planes – 110, 112, 123, and 134 – in two refractory multi-principal element alloys (MPEAs): MoNbTi and NbTiZr. To serve as a reference material for MoNbTi, we develop, validate, and employ an A -atom interatomic potential, which is expected to represent the response of the nominal random solution. Our calculations show that, owing to the variation in local chemical composition within small finite nanometer sized planes, (i) the peak GSFE values vary significantly among parallel planes; (ii) within the same specific 110 plane, substantial differences in the GSFE curves along the two non-parallel 111 directions are observed; (iii) the 110 GSFE curves develop an asymmetry, such that the peak energy is not achieved at half the lattice periodicity length, (iv) the GSFE value after a shift equaling the lattice periodicity length is not recovered; and (v) on average, the peak GSFE values are close to the volume fraction average of the peak GSFEs of their constituents. Highlights: Generalized stacking fault energies in MoNbTi and NbTiZr are calculated. Molecular static simulations and density functional theory calculations are conducted. A new interatomic potential for MoNbTi is developed and validated.